Molecular study on the Atlanto-Mediterranean rocky-shore ichthyofauna : the potential of DNA markers in the study of phylogenis, biogeography, ecology and the evolution of behaviour - Almada, Frederico (2010)
Tese de doutoramento em Biologia (Biologia Evolutiva) apresentada à Universidade de Lisboa através da Faculdade de Ciências, 2009